Best practices of interoperability among heterogeneous software systems: a Semat-based representation (2016)
Interoperability among heterogeneous software systems is a software quality sub-characteristic. Some methods for dealing with interoperability exhibit differences in aspects like generality, development method, and work products, among others. However, some authors understand interoperability as a non-functional requirement with general-purpose practices for identifying and specifying such requirement. Other authors assess and achieve interoperability by using work products falling beyond defined practices. Consequently, in this paper we propose four best practices in order to accomplish interoperability among heterogeneous software systems. Our best practices are represented with the Semat (Software Engineering Method and Theory) kernel, since it includes a language with simple and precise elements. Definition of interoperability best practices enables unification of the effort focused on software systems interoperability.